The (un)constitutionality of the COVID-19 health passport: An analysis under the medico-legal approach - Ovando , Rômulo Gustavo de Moraes; Ovando , Luiz Alberto (Seven Editora, 2023)
The work aims to analyze, from the perspective of Medicine and Law, the possibilities of relativizations - and even suppressions - of fundamental rights and guarantees in the face of the global health crisis imposed by the coronavirus (COVID-19). The pandemic, in general, has implemented numerous restrictions aimed at the gradual opening of the economy and the consequent return to normalcy. However, these limitations, however necessary they may be considered, have also led to violations of the constitutional rights of citizens, under the pretext of promoting the well-being of the social body. Thus, the justification of the thematic relevance is based on the consequences of the sophistry that the COVID-19 health passport, imposed by the public authorities, may cause for society, especially in the absence of previous and/or technical parameters capable of proving the effectiveness of the measure, which is extremely burdensome and flirts with the state of exception. The so-called COVID-19 health passport is problematic, that is, to examine the motivation of the State to relativize and even suppress the guarantees and individual freedoms of those who are deliberately affected by such a measure. The objective of this study is to demonstrate that the COVID-19 health passport, because it is an atypical measure, cannot be used haphazardly by the Government, under penalty of causing social segregation, since they privilege certain groups to the detriment of others, in addition to focusing on evident abuse of power. The methodology used was bibliographical, with a selection of books, articles, legal and jurisprudential texts and news extracted from official journals. The most important results of the study indicate that the health passport, at first, sought to implement the standardization of vaccination, however, in the background, it began to be used as a discriminatory measure. Finally, it is imperative to highlight that research cannot be equated with the anti-vaccine movement, much less be understood as a way of encouraging non-vaccination, on the contrary, the proposed approach aims to demonstrate that public policies should be based on humanization, and not on disrespect for rights, freedom and fundamental guarantees. DOI:https://doi.org/10.56238/globalhealthprespesc-007